2012
DOI: 10.1128/aem.01303-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Symbiotic Diversity of Nitrogen-Fixing Bacteria Isolated from Agricultural Soils in the Western Amazon by Using Cowpea as the Trap Plant

Abstract: ABSTRACTCowpea is a legume of great agronomic importance that establishes symbiotic relationships with nitrogen-fixing bacteria. However, little is known about the genetic and symbiotic diversity of these bacteria in distinct ecosystems. Our study evaluated the genetic diversity and symbiotic efficiencies of 119 bacterial strains isolated from agriculture soils in the western Amazon using cowpea as a trap plant. These strains were clustered into 11 cultural groups according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(51 citation statements)
references
References 20 publications
3
43
0
5
Order By: Relevance
“…This bacterium is one of the genera belonging to betaproteobacteria, which have been reported as legume nodulating bacteria for the fi rst time by Benata et al (2008). A. xylosoxidans formed root nodule in Prosopis julifl ora (Benata et al, 2008); Mucuna bracteata (Salwani et al, 2012); and cowpea (Guimarães et al, 2012). In this study, we also confi rmed the existence of nifH and nodA copy genes.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…This bacterium is one of the genera belonging to betaproteobacteria, which have been reported as legume nodulating bacteria for the fi rst time by Benata et al (2008). A. xylosoxidans formed root nodule in Prosopis julifl ora (Benata et al, 2008); Mucuna bracteata (Salwani et al, 2012); and cowpea (Guimarães et al, 2012). In this study, we also confi rmed the existence of nifH and nodA copy genes.…”
Section: Introductionsupporting
confidence: 57%
“…40 days after cultivation of soybean, observation showed that UGM48a formed nodule (Table 3). A. xylosoxidans has previously been reported having ability to nodulate Prosopis julifora (Benata et al, 2008); cowpea (Guimarães et al, 2012); and Mucuna bracteata (Salwani et al, 2012). This is the fi rst fi ndings that A. xylosoxidans were able to nodulate soybean.…”
Section: Nodulation Assay In Glycine Max (L) Merr Var Wilismentioning
confidence: 99%
“…é uma leguminosa de grande importância agrícola, por ser uma das principais fontes de proteína vegetal e contribuir de forma significativa para a geração de renda no campo, nas regiões Norte e Nordeste do Brasil. Essa espécie é capaz de beneficiar-se amplamente da FBN e tem sido bastante utilizada como planta-isca em estudos de diversidade de BFNNL, em razão da sua capacidade de formar simbiose com diversos gêneros e espécies de bactérias (Moreira, 2006;Guimarães et al, 2012). Além disso, foi relatado o isolamento de bactérias não simbióticas, em nódulos de feijão-caupi, com grande potencial de promoção do crescimento vegetal (Marra et al, 2012).…”
Section: Methodsunclassified
“…bras., Brasília, v.48, n.9, p.1275-1284, set. 2013 DOI: 10.1590/S0100-204X2013000900012 a identificação de estirpes pertencentes aos gêneros Bradyrhizobium e Rhizobium, provenientes de nódulos de feijão-caupi (Guimarães et al, 2012;Jaramillo et al, 2013). Contudo, os gêneros Paenibacillus e Bacillus geralmente são endofíticos de nódulos, mas não nodulíferos, embora haja relatos da nodulação em feijão-caupi por esses dois gêneros (Marra et al, 2012;Jaramillo et al, 2013).…”
Section: Estirpesunclassified
See 1 more Smart Citation